Influences on consumers decisions to buy new cars in Cacoal, Brazil - do Vale, Lucélia Largura; Vidigal Filho, Ademir Luiz; Piacentini, Marcos Tadeu Simões; Piacentini, Alexandre Leonardo Simões; Piassarolo, Vanessa Coelho (International Journal for Innovation Education and Research, 2019)
Regardless of the changes in the economy of the country in recent years caused by the global financial crisis, Brazil has managed to stand positively, despite the many variations in the national and international economic scenario. In the rise of the economy, the automobile sector was a prominent contributor, making it more advantageous for a consumer to purchase a new vehicle. This article aims to study the factors in the city of Cacoal that influenced a consumer’s decision to buy a new car. The methodology was descriptive research, using the deductive method, a qualitative and quantitative approach, and bibliographic research. To collect our data, we used a questionnaire containing 14 questions, some semi-open and some multiple-choice closed, sent in a link via email and Whatsapp, with the help of the Google Forms tool. In our results, it was observed that a consumer’s buying behaviour receives influences from both the external environment and the social group, both of which have a direct impact on the process of deciding to buy a new vehicle. The digital media, in the form of specialized electronic magazine websites, have become popular for consumers to consult. It was found that consumers researching in order to make a purchase decision consider the following decision factors first: quality, trust in technical assistance, confidence in the brand, safety and finally price. To a consumer looking for a new car these items are found to be the most important. The present study aims to set the parameters for future studies and to justify an interest in research.